Oana Panaïté. The Colonial Fortune in Contemporary Fiction in French. Liverpool: Liverpool UP, 2017. - Nanar Khamo (Studies in 20th & 21st Century Literature, 2018)
Review of Oana Panaïté. The Colonial Fortune in Contemporary Fiction in French. Liverpool: Liverpool UP, 2017. 206 pp.
Keywords: colonialism; postcolonialism; French fiction